Social Media-Based Sentiment Analysis: Electric Vehicle Usage in Indonesia - Salsabila, Helmi; Habibi, Roni; Harani, Nisa Hanum (AI Society & STMIK Indonesia, 2023)
This research analyzes the sentiment regarding the use of electric vehicles in Indonesia through social media, utilizing over 10,000 data points from Twitter. The results indicate a variation of positive, negative, and neutral sentiments towards electric vehicles on social media. Female users play a significant role in expressing their views and actively participating in discussions related to electric vehicles. The locations with the highest user activity discussing electric vehicles are Indonesia, DKI Jakarta, Makassar, Tangerang, and Karawang. The peak activity was observed in September 2019, suggesting a significant interest in electric vehicles. The SVM algorithm achieved an accuracy of 88% for positive and neutral sentiments, but performed relatively lower for negative sentiments. This research lacks data on the gender and age of the respondents. Future studies should address these shortcomings to gain a deeper understanding of public perceptions regarding electric vehicles in Indonesia.